Peningkatan Kecerdasan Logika-Matematika Melalui Biblioterapi Pada Anak Usia Dini Kelompok A Kober Warna Plus - Wanti Setiawati (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
The background of this research is the lack of logic-mathematical abilities of children, especially knowing the symbol of group A numbers in Kober Warna Plus. For this reason, bibliotherapy methods are needed to develop logical-mathematical intelligence This research method is descriptive and research form PTK with pre-school child subjects. Data collection techniques are observation, interviews, and documentation. Based on the results of the first cycle test and observation study of 12.5% of the children developed very well, 37.5% developed according to expectations, and 50% began to develop and still had to be stimulated, but when the second cycle was tested, the result showed that the child had developed ability very good, namely 87.5%, and 12.5% as expected.